Flamingo bar stool / Muhammad Mifdhal Danial Mohd Fadzli - Mohd Fadzli, Muhammad Mifdhal Danial (Universiti Teknologi MARA, Kedah, 2025)
Flamingos, a symbol of elegance, are featured in an elevated design. Inspired by the beautiful poise and vivid presence of flamingos, this idea takes flight into the realm of furniture design like a bird in the sky. The collection of bar stools that combine refinement and a whimsical edge is inspired by their one-of-a-kind balance and stunning silhouette, which serve as the inspiration for the collection. By harnessing the delicate lines of flamingo legs and the curvature of their exquisite bodies, these bar stools enhance more than just your seating they provide a bit of the wild, a dash of color, and a sense of artistry to your area. A lightweight yet durable frame that embodies the sense of flamingo-like elegance is featured in each piece, which is designed to convey both beauty and usefulness.